CALL THE ISLAMIC INVASIONS IN THE POETRY OF D. MUHAMMED SIAM - Wissam Mezher Abdul Hamid Al-Rawiand Shaker Mahmoud Abdul Saadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Our Islamic history represents a record full of great travels and heroisms that were the focus of admiration and interest for Islamic poets in the modern era, including our poet Dr. Muhammad Siam - may God have mercy on him. His poetic output abounded. By mentioning those glorious Islamic conquests and conquests that represented the immortal heritage lesson that the present generation should draw upon and benefit from its lessons so that it can rise from its slumber and regain its glory and honor that was lost due to weakness in front of enemies and distance from the values and principles of Islam. The poet drew from the specifics of this glorious Islamic history, and benefited from it in his poetic experiences, which he was able to convey to us in a smooth manner far from complexity, in which he committed to cultural communication between the past and the present through a balanced view through which he proved that his committed poetry keeps pace with all times and eras. The poet, with what he recalled of the details of battles and events, proved that if the Islamic nation wants to rise from its repression, it must stir its historical memory, and evoke the glories and heroisms of its ancestors; To draw lessons and lessons from it that will improve its present and anticipate its future.